(untitled) (Ustozlar uchun, 2025)
Abstract:The cardiovascular system plays a critical role in maintaining tissue perfusion and overall homeostasis. Pathophysiological alterations in this system can lead to various cardiovascular diseases (CVDs), which remain leading causes of morbidity and mortality worldwide. This article reviews key mechanisms underlying cardiovascular pathologies, including endothelial dysfunction, atherosclerosis, hypertension, myocardial ischemia, and heart failure. Understanding these mechanisms is vital for developing effective prevention and treatment strategies.